Chemical Composition of Pterospermum heterophyllum Root and its Anti-Arthritis Effect on Adjuvant-Induced Arthritis in Rats via Modulation of Inflammatory Responses - Yang, Li; Liu, Ronghua; Fan, Aiguo; Zhao, Jingjing; Zhang, Yong; He, Junwei (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease with no effective and beneficial drugs. Many traditional folk medicines have been proven to be effective to treat RA. Among these, the root of Pterospermum heterophyllum Hance (PH) has been widely used as a traditional remedy against RA in China with no scientific validation. This study aimed to investigate the chemical compositions and therapeutic effect of PH on adjuvant-induced arthritis (AIA) model in rats for the first time. 73 compounds were identified from PH based on ultra-pressure liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-qTOF-MS/MS), and flavonoids may be partly responsible for the major anti-arthritic effect. In parallel, the PH extracts at 160, 320 and 640 mg/kg/day were orally administered to rats for 22 days after post-administration adjuvant. The results showed that PH remarkably ameliorated the histological lesions of knee joint, increased body weight growth, decreased arthritis score, reduced thymus and spleen indices in model rats. Moreover, PH treatment persuasively downregulated the levels of rheumatoid factor (RF), C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), IL-6, IL-17, cyclooxygenase-2 (COX-2), 5-lipoxygenase (5-LOX) and matrix metalloproteinase-2 (MMP-2), and observably upregulated IL-4 and IL-10 levels in model rats. These findings demonstrated that PH possessed prominent anti-RA effect on AIA rats via modulation of inflammatory responses, and to support the traditional folk use of this plant.